Economic valuation of attributes of Lake Tana: random parameter model - Asmamaw Getnet (Elsevier, 2021)
The general objective of the study is estimating economic value of Lake Tana attributes using stated preference method of valuation in general and choice experiment method in particular. The target population was households who live around Lake Tana. The study has identified four attributes of Lake Tana (Water quality, fishery, irrigation, and recreation). The study has formulated three alternatives in which two of them were improved whereas the one is the status quo. Each attribute has three levels. The study has surveyed 238 households which were selected using multistage sampling method. Each respondent was presented with eight choice sets. Each choice set has three alternatives including opt option. The study has employed random parameter logit model for data analysis. In line with this model the study has conducted the extended random parameter logit model. The status quo (ASC0) is negative and significant both in random parameter logit model but positive and insignificant in extended random parameter logit model. This means that households have preferred the improved situation of the Lake Tana. This indicates that households are willing to pay to improve the current situation of the lake. Random parameter logit model shows that all improved attributes have positive sign and significant at 1% significance level. This means that improved situation of attributes that are identified by this study improve utility of households. Government should protect Lake Tana from any problem by raising funds from households since households are willing to pay to improve Lake Tana's attributes.